2007
DOI: 10.1073/pnas.0705971104
|View full text |Cite
|
Sign up to set email alerts
|

Activin A is a critical component of the inflammatory response, and its binding protein, follistatin, reduces mortality in endotoxemia

Abstract: Activin A is a member of the transforming growth factor-␤ superfamily, which we have identified as having a role in inflammatory responses. We show that circulating levels of activin increase rapidly after LPS-induced challenge through activation of Toll-like receptor 4 and the key adaptor protein, MyD88. Treatment with the activin-binding protein, follistatin, alters the profiles of TNF, IL-1␤, and IL-6 after LPS stimulation, indicating that activin modulates the release of several key proinflammatory cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
234
5
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(259 citation statements)
references
References 37 publications
(32 reference statements)
19
234
5
1
Order By: Relevance
“…Of note, activin-A induces the generation of mouse regulatory T cells suppressive against responses by other T cells in vitro and in vivo (5,35). By contrast, certain studies point to proinflammatory effects of activin-A as shown by enhanced survival during systemic administration of follistatin following a lethal dose of LPS in vivo (8). Moreover, increased TNF-α and IL-1β release was observed upon stimulation of rat macrophages with activin-A in vitro (42).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Of note, activin-A induces the generation of mouse regulatory T cells suppressive against responses by other T cells in vitro and in vivo (5,35). By contrast, certain studies point to proinflammatory effects of activin-A as shown by enhanced survival during systemic administration of follistatin following a lethal dose of LPS in vivo (8). Moreover, increased TNF-α and IL-1β release was observed upon stimulation of rat macrophages with activin-A in vitro (42).…”
Section: Discussionmentioning
confidence: 95%
“…Although previous studies have demonstrated induction of activin-A during infections in animal models and in adults (6)(7)(8)22,23), as far as we know, this is the first study that investigated activin-A expression in neonates. We demonstrate that activin-A is significantly increased in the serum of neonates during infections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A closer examination of these pathways revealed 2 of the 14 connections could bear relevance in the context of feather generation. The first of these is a pathway that connects follistatin with the localization of the tumor necrosis factor-a protein (Jones et al, 2007), which in turn decreases the activation of Collagen-a-2(I) in human dermal fibroblasts (Yamane et al, 2003). The second putatively relevant pathway was one that showed follistatin Figure 3 The relationship between pairwise F ST values for SNP markers and microsatellites with the same population pairs (see Lehtonen et al, 2009a).…”
Section: Resultsmentioning
confidence: 99%